TEKNIK PRODUKSI KEPITING BAKAU Scylla serrata BERBASIS LAUT PULAU DI DESA TUHAHA, KECAMATAN SAPARUA TIMUR KABUPATEN MALUKU TENGAH - Pattiasina, Bethsy Jane; Pattinasarany, Maureen Mercy; Loupatty, Joice Welly; Jamal, Endang; Pattipeilohy, Christian Ernsz; Rijoly, Stefanno Markus Anthony (Jurnal Abdi Insani, 2025)
Mangrove crab is one of the leading export commodities and has high economic value. The increasing demand for mangrove crab exports has created new problems, namely the availability of seeds and the consumption size of this mangrove crab. Mangrove crab cultivation in Indonesia until now still depends on natural stocks, so it is necessary to review the development of sustainable mangrove crab cultivation. This community service activity was attended by 43 participants consisting of 6 teaching staff of the Department of Aquaculture, Faculty of Fisheries, Unpatti, and 37 people from Negeri Tuhaha. The stages carried out include delivering material on the types of mangrove crabs, direct introduction to the types of mangrove crab maintenance and enlargement containers, implementation of crab cultivation containers using the tancap and keramba methods, as well as discussions and questions and answers.